Preliminary Study On Bioceramics Containing Gallic Acid - Kamarudin, Farrah Izzatul Ain (2020)
The aims of this study are to investigate the probability of Gallic Acid to be introduced into different type bioceramic materials such as HAp, α -TCP and β -TCP. To achieve this aims, soaking time of bioceramics in gallic acid solution and concentration of gallic acids were varies to understand these factors during preparation of bioceramics containing gallic acids. The compositional, surface morphologies, functional group, surface topography and hardness of specimens were analysed using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), Atomic Force Microscope (AFM) and Vickers hardness test, respectively. The results obtain showed that the presence of gallic acid in bioceramic specimens cannot be detected even soaking in gallic acid solution for 5, 10 and 15 mins but there is increasing of HAp weight and density after soaking in Gallic acid solution. On contrary, when increasing the concentration of gallic acid solution up to 0.15 mol/L, the formation of Gallic crystals was observed using SEM on the surface of α-TCP and β -TCP after exposing with this solution for 5 mins. Moreover, HAp bioceramic shows gaining in term of weight and density while α-TCP and β -TCP shows opposite result. Besides, the different in bioceramics porosity also play crucial role which may occur due to different sintering temperature of each bioceramic. Therefore, this preliminary study shows some insight regarding the parameters that need to be adjusted in fabricating bioceramic materials containing gallic acid.